Synchronized Diabetes Monitoring System: Development of Smart Mobile Apparatus for Diabetes Using Insulin - Kahraman, Mustafa; Dudukcu, Hatice Vildan; Kurt, Serkan; Yildiz, Huseyin; Aydin, Nizamettin; Mutlu, Ummu; Cakmak, Ramazan; Boz, Elif Beyza; Ozbek, Hasan Ediz; Erturk, Mehmet Ali; Ozogur, Gokhan; Ozogur, Hatice Nizam; et al. (ELSEVIER SCIENCE INC, 2024)
Accurate and timely injection of insulin doses in accordance with the treatment protocol is very important in the follow-up of insulin-dependent diabetes patients. In this study, a new smart mobile apparatus (SMA) has been developed. The SMA can be attached to insulin pens and record and transfer data by detecting the patient's dose of insulin and the time at which it was provided. The SMA can detect the dose determined in the insulin pen through linear capacitive sensors. Electronic parts and sensor mechanism are located on the designed SMA body. The insulin pen's two-part mechanical construction of the body senses movement during dosage adjustment while also making sure the dose information is recorded in the control unit. The dose and time information recorded in the SMA internal memory are transmitted to the patient's smartphone via the developed mobile application. The developed SMA prototypes were evaluated by a team of doctors in a hospital setting for three months. As a result of the three-month study, it was observed that the insulin dose and administration times could be accurately sent to the smartphone application via SMA. The SMA was created in the laboratory environment and was prepared for pilot research with insulin-dependent diabetes patients in a hospital setting. It was observed that the SMA prototype successfully identified and recorded the dose and timing of the patient's self-administered insulin. (c) 2024 AGBM. Published by Elsevier Masson SAS. All rights are reserved, including those for text and data mining, AI training, and similar technologies.
Keywords: SMA helps users to control blood sugar; Diabetes mellitus; Wearable health technologies; Patient monitoring; Insulin dose tracking; Smart mobile apparatus; DOSE-MEMORY; PEN; Engineering